Ranked set sampling : 65 years improving the accuracy in data gathering - Bouza Herrera, Carlos Narciso, 1942-; Al-Omari, Amer Ibrahim Falah (Academic Press, 2019)
Ranked Set Sampling: 65 Years Improving the Accuracy in Data Gathering is an advanced survey technique which seeks to improve the likelihood that collected sample data presents a good representation of the population and minimizes the costs associated with obtaining them. The main focus of many agricultural, ecological and environmental studies is the development of well designed, cost-effective and efficient sampling designs, giving RSS techniques a particular place in resolving the disciplinary problems of economists in application contexts, particularly experimental economics. This book seeks to place RSS at the heart of economic study designs. Focuses on how researchers should manipulate RSS techniques for specific applicationsDiscusses RSS performs in popular statistical models, such as regression and hypothesis testingIncludes a discussion of open theoretical research problemsProvides mathematical proofs, enabling researchers to develop new models.